The post-roman occupation of the northern courtyard of the sanctuary of Baalshamin in Palmyra: a reassessment of the evidence based on the documents in the ‘Fonds d’Archives Paul Collart, Université de Lausanne’ - Intagliata, Emanuele Ettore (Zeitschrift für Orient-Archäologie, 2016)
This paper presents a reassessment of the occupational evidence from Late Antiquity and the Early Islamic Period within the Grande Cour of the Sanctuary of Baalshamin in Palmyra. The study is based on a renewed analysis of the excavation documentation kept at the Fonds d’Archives Paul Collart (Université de Lausanne).